Principles of Physics For Scientists and Engineers - Radi, Hafez A .; Rasmussen, John O.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This textbook presents a basic course in physics to teach mechanics, mechanical properties of matter, thermal properties of matter, elementary thermodynamics, electrodynamics, electricity, magnetism, light and optics and sound. It includes simple mathematical approaches to each physical principle, and all examples and exercises are selected carefully to reinforce each chapter. In addition, answers to all exercises are included that should ultimately help solidify the concepts in the minds of the students and increase their confidence in the subject. Many boxed features are used to separate the examples from the text and to highlight some important physical outcomes and rules. The appendices are chosen in such a way that all basic simple conversion factors, basic rules and formulas, basic rules of differentiation and integration can be viewed quickly, helping student to understand the elementary mathematical steps used for solving the examples and exercises. Instructors teaching form this textbook will be able to gain online access to the solutions manual which provides step-by-step solutions to all exercises contained in the book. The solutions manual also contains many tips, colored illustrations, and explanations on how the solutions were derived.
Part 1: Fundamental Basics -- Units and Dimensions -- Vectors -- Part 2: Mechanics -- Motion in One Dimension -- Motion in Two Dimensions -- Force and Motion -- Work, Energy, Momentum, Power, Gravitation -- Mechanical Properties of Matter -- Part 3: Thermodynamics -- Heat and the Laws of Thermodynamics -- Thermal Properties of Matter -- Kinetic Theory of Gases -- Part 4: Sound and Light Waves -- Oscillations and Wave Motion -- Sound Waves -- Superposition of Sound Waves -- Light Waves and Optics -- Interference, Diffraction, and Polarization of Light -- Part 5: Electricity -- Electric Force and Fields -- Gauss$1 (Bs Law -- Electric Potential -- Capacitors and Capacitance -- Electric Circuits -- Part 6: Magnetism -- Magnetic Field -- Sources of the Magnetic Field -- Faraday$1 (Bs Law -- Inductance.s
Keywords: Physics; Mechanics; Magnetism; Mechanical engineering; Computer engineering; Physics; Classical Continuum Physics; Mechanics; Optics and Electrodynamics; Magnetism, Magnetic Materials; Mechanical Engineering; Electrical Engineering